Transformacija meščanske zavesti v Kamniku - Klobčar, Marija (Traditiones (Ljubljana), 2001)
Middle-class awareness is one of the most pronounced characteristics of the middle classes living in Kamnik. This awarenss was largely based on the citizenship rights which in the 19th century were protected by a speciall institution, the so-called Civic Corporation of Kamnik (Meščanska korporacija). This paper examines the confrontation of this awareness with national awareness, their interdependence, and their differences. WWII, and especially the period that followed, brought about marked social changes. This was the time in which middle-class awareness was subjected to transformation and no longer posed a threat to others. Political changes of the 1990's brought on changes in poeple's lives. Because of these changes, increasing urbanisations and doubtful urbanistic interventions the need to revitalize the town, and with that also the necessity to form an awareness which would enable such revitalization and give it sense, once again arose
Keywords: ethnology; etnologija; meščani; Slovenia; Slovenija; Kamnik